The influence of religious coping on family resilience in family interactions during the COVID-19 pandemic - Yoyok Bekti Prasetyo; Dinda Dwi Savira; Nur Lailatul Masruroh; Faridi Faridi (Universitas Aisyah Pringsewu, 2023)
Background: Religious coping is very important in overcoming difficult problems in the family. This study aims to analyze the influence of religious coping on family resilience in family interactions during the COVID-19 pandemic.Methods: The research design used is descriptive with a cross-sectional survey approach. Two hundred and forty-two villagers in East Java Province, Indonesia were respondents in this study. Data collection by questionnaire, data analysis using binary logistic regression and multivariate logistic regression. The degree of freedom used is 95% with a standard error of 0.05.Result: Religious coping and education influence family resilience in interacting. Families with adequate religious coping will have 1 time chance of having resilience in interacting compared to families with inadequate religious coping (OR: 1.059; 95% CI: 1.019 – 1.101). Families who work will have a 0.8 times chance of having resilience in interacting compared to families who do not work (OR: 0.759; 95% CI: 0.572 – 1.006). Conclusion: Religious coping factors strongly influence family resilience in utilizing socioeconomic resources. Strengthening the community with a religious approach is needed to support the family's line of defense against this pandemic condition.